The radiation environment near the lunar surface: CRaTER observations and Geant4 simulations. Issue 4 (3rd April 2013) - Looper, M. D.; Mazur, J. E.; Blake, J. B.; Spence, H. E.; Schwadron, N. A.; Golightly, M. J.; Case, A. W.; Kasper, J. C.; Townsend, L. W.
Abstract : At the start of the Lunar Reconnaissance Orbiter mission in 2009, its Cosmic Ray Telescope for the Effects of Radiation instrument measured the radiation environment near the Moon during the recent deep solar minimum, when galactic cosmic rays (GCRs) were at the highest level observed during the space age. We present observations that show the combined effects of GCR primaries, secondary particles ("albedo") created by the interaction of GCRs with the lunar surface, and the interactions of these particles in the shielding material overlying the silicon solid‐state detectors of the Cosmic Ray Telescope for the Effects of Radiation. We use Geant4 to model the energy and angular distribution of the albedo particles, and to model the response of the sensor to the various particle species reaching the 50 kilometer altitude of the Lunar Reconnaissance Orbiter. Using simulations to gain insight into the observations, we are able to present preliminary energy‐deposit spectra for evaluation of the radiation environment's effects on other sensitive materials, whether biological or electronic, that would be exposed to a similar near‐lunar environment. Key Points: CRaTER measured GCRs and lunar Geant4 models of sensor response and albedo help us understand the observations We extract LET spectra over a broad energy deposit range from the measurements